Risk of Skin Cancer among Patients with Chronic Kidney Disease Treated with Ultraviolet B Phototherapy for Uraemic Pruritus: A Nationwide Cohort Study - Mei-Ju Ko; Jenq-Wen Huang; Hon-Yen Wu; Wan-Chuan Tsai; Le-Yin Hsu; Ping-Hsiu Tsai; Kuo-Liong Chien; Kuan-Yu Hung (Medical Journals Sweden, 2021)
The safety of ultraviolet B (UVB) phototherapy with respect to cutaneous carcinogenesis has not been established for patients with chronic kidney disease. To investigate this issue, a nationwide cohort study of 10,805 patients with advanced chronic kidney disease was conducted using data from the National Health Insurance of Taiwan, the Taiwan Cancer Registry, and the national death registry. After a median follow-up of 75 months, 16 of 2,161 patients in the UVB group and 63 of 8,644 patients in the non-UVB group developed skin cancers. Compared with the non-UVB group, patients in the UVB group did not show an increased risk of skin cancer (hazard ratio 1.066; 95% confidence interval 0.584-1.944), non-melanoma skin cancer (hazard ratio 1.067; 95% confidence interval 0.571-1.996), or cutaneous melanoma (hazard ratio 1.009; 95% confidence interval 0.115-8.879). In addition, patients who received more UVB phototherapy did not show an increased risk of skin cancer. UVB phototherapy appears to be a safe treatment for uraemic pruritus in patients with chronic kidney disease.